Analisis Dominasi Bahasa Formal dan Gaul Dalam Komunikasi Masyarakat Jakarta Studi Kasus Stasiun Pasar Senen Jakarta - Hasanul Hafli; Sugeng Sugeng; Sahrul Muzekki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2025)
Jakarta, as a multicultural city, presents a complex linguistic dynamic, particularly between formal and colloquial (slang) language. This study aims to analyze the dominance of these two language varieties at Pasar Senen Station and identify the factors influencing their use. This research employs a qualitative approach with a case study design, involving observation, semi-structured interviews, visual and audio documentation, and social media analysis. The findings indicate that formal language dominates official domains such as announcements and ticket transactions, while slang is more frequently used in casual interactions among young passengers and between vendors and customers. Code-switching and code-mixing are common communication strategies, while social media plays a significant role in accelerating the spread of slang vocabulary in public spaces. In conclusion, language choice at Pasar Senen Station is influenced by interaction context, age, social status, communication purposes, and digital culture. Language functions not only as a communication tool but also as a marker of identity and solidarity in urban society.